Carbon(sp2)‐carbon(sp3) Bond‐forming Cross‐coupling Reactions Using Sulfur‐Modified Au‐Supported Nickel Nanoparticle Catalyst. Issue 9 (13th July 2022) - Ohta, Ryousuke; Shio, Yasunori; Akiyama, Toshiki; Yamada, Makito; Shimoda, Shuhei; Harada, Kazuo; Sako, Makoto; Hasegawa, Jun‐ya; Arisawa, Mitsuhiro
Abstract: We report a carbon(sp 2 )‐carbon(sp 3 ) bond‐forming cross‐coupling reactions by employing a nano‐size nickel catalyst supported on sulfur‐modified gold (SANi). This transformation demonstrates an efficient synthesis of functionalized aryl compounds, including heterocycles. Notably, the reactions proceeded in good yields with significantly low leaching of nickel from SANi. Moreover, SANi could be recycled several times without significant loss of catalytic activity. Abstract : Carbon(sp 2 )‐carbon(sp 3 ) bond‐forming cross‐coupling reactions by employing a nano‐sized nickel catalyst supported on sulfur‐modified gold (SANi) has been reported.